Genetic predisposition for increased red blood cell distribution width is an early risk factor for cardiovascular and renal comorbidities - Xi Cheng; Blair Mell; Ahmad Alimadadi; Sarah Galla; Cameron G. McCarthy; Saroj Chakraborty; Venkatesha Basrur; Bina Joe (The Company of Biologists, 2020)
Red blood cell distribution width (RDW) is a measurement of the variation in size and volume of red blood cells (RBCs). Increased RDW, indicating a high heterogeneity of RBCs, is prominently associated with a variety of illnesses, especially cardiovascular diseases. However, the significance of this association to the onset and progression of cardiovascular and renal diseases is unknown. We hypothesized that a genetic predisposition for increased RDW is an early risk factor for cardiovascular and renal comorbidities. Since there is no known animal model of increased RDW, we examined a CRISPR/Cas9 gene-edited rat model (RfflTD) that presented with features of hematologic abnormalities as well as severe cardiac and renal comorbidities. A mass spectrometry-based quantitative proteomic analysis indicated anemia of these rats, which presented with significant downregulation of hemoglobin and haptoglobin. Decreased hemoglobin and increased RDW were further observed in RfflTD through complete blood count. Next, a systematic temporal assessment detected an early increased RDW in RfflTD, which was prior to the development of other comorbidities. The primary mutation of RfflTD is a 50 bp deletion in a non-coding region, and our study has serendipitously identified this locus as a novel quantitative trait locus (QTL) for RDW. To our knowledge, our study is the first to experimentally pinpoint a QTL for RDW and provides a novel genetic rat model mimicking the clinical association of increased RDW with poor cardio-renal outcome.